1999
DOI: 10.1161/01.hyp.33.1.290
|View full text |Cite
|
Sign up to set email alerts
|

Genes Encoding Atrial and Brain Natriuretic Peptides as Candidates for Sensitivity to Brain Ischemia in Stroke-Prone Hypertensive Rats

Abstract: -Previous studies suggested that atrial natriuretic peptide gene (Anp) and brain natriuretic peptide gene (Bnp) are plausible candidate genes for susceptibility to stroke and for sensitivity to brain ischemia in the stroke-prone spontaneously hypertensive rat (SHRSP). We performed structural and functional analyses of these 2 genes in SHRSP from Glasgow colonies (SHRSPGla) and Wistar-Kyoto rats from Glasgow colonies (WKYGla) and developed a radiation hybrid map of the relevant region of rat chromosome 5. Seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…A recent study 34 that examines the possible role of ANP in stroke in the rat and fails to find evidence for such a contribution is actually quite consistent with our observations: in this study, SHRSP and WKY rats subjected to middle cerebral artery occlusion showed no differences in brain ANP expression. Of note, there was no difference between the ANP genes of the two strains used with regard to sequence, structure, and functional parameters, as demonstrated previously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study 34 that examines the possible role of ANP in stroke in the rat and fails to find evidence for such a contribution is actually quite consistent with our observations: in this study, SHRSP and WKY rats subjected to middle cerebral artery occlusion showed no differences in brain ANP expression. Of note, there was no difference between the ANP genes of the two strains used with regard to sequence, structure, and functional parameters, as demonstrated previously.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, there was no difference between the ANP genes of the two strains used with regard to sequence, structure, and functional parameters, as demonstrated previously. 34 An earlier, erroneous interpretation that stroke in an intercross of SHRSP and WKY rats was linked to the ANP locus 35 was indeed corrected by additional data on chromosomal localization of ANP in this recent report. 34 Although the present data support the notion that ANP may indeed be a candidate gene for contribution to stroke given its localization within the stroke-linked locus STR2, final validation of this result must be based on congenic and positional cloning experiments, which are in progress.…”
Section: Discussionmentioning
confidence: 82%
“…Plasma levels of BNP have previously been described as elevated in the acute phase of stroke, 16,17 and some authors have suggested that BNP levels are correlated with neurologic deficits. 17,18 However, although in our study BNP also showed a slight correlation with the NIHSS score, it remained an independent predictor of cardioembolic etiology after correcting for stroke severity and extent.…”
Section: Bnp and Dd For Cardioembolic Strokementioning
confidence: 99%
“…39 It should be noted that this QTL colocalizes with the blood pressure QTL observed in studies on Dahl S rats. 19,26 It appears that there are 2 separate QTL for stroke on rat chromosome 5 40 and a blood pressure QTL that might be either related or unrelated to one of these stroke QTL. 19 A current comprehensive review by Rapp 19 provided a unifying speculation to explain the coexistence and colocalization of the blood pressure-independent stroke QTL and the blood pressure QTL on rat chromosome 5.…”
Section: Experimental Models Of Genetic Hypertensionmentioning
confidence: 99%